Hyper-Personalization For Customer Innovativeness, Customer Involvement and Adoption Intention - Alfian, Rendi; Yuliana, Lingga; Perkasa, Didin Hikmah; Putra, Muhammad Farrel Risyawal (Widya Cipta: Jurnal Sekretari dan Manajemen, 2025)
In the context of smartphone product uptake, this study attempts to investigate how hyper-personalization can affect customer innovativeness and customer involvement. Businesses can offer features and information that are customized to each customer's tastes by using a hyper-personalization strategy, which can raise customer engagement and interest in using the product. Taking samples with 100 responders is possible using the purposeful sampling technique. Smartphone users in South Jakarta between the ages of 17 and 50 met the requirements to participate in this study. July 5–6, 2024, was the date of data gathering. Primary data sources are the source of the data. Google Form serves as an intermediary in the distribution of primary data in the form of a questionnaire. Smart PLS version 4.1.0.0 is a data processing program that may be used to analyze data using the partial least squares technique. The outcomes of the research support the first hypothesis, which holds that adopt intention is influenced by consumer innovation. The impact of consumer innovativeness on customer involvement is demonstrated by the second hypothesis. The research's managerial implications include the possibility for businesses in the smartphone sector to keep introducing innovative items to market as a result of the public's approval of new products. Consumers anticipate new products since they are accustomed to using smartphones.